2008
DOI: 10.1016/j.atherosclerosis.2007.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function properties of the apoE-dependent COX-2 pathway in vascular smooth muscle cells

Abstract: Apolipoprotein (apoE) E is a multifunctional protein that plays a critical role in atherogenesis, in part by regulating the intimal proliferation of vascular smooth muscle cells. Recently, a novel cyclooxygenase (COX)-2 pathway was shown to contribute to the anti-proliferative action of human apoE3 in vascular smooth muscle cells (VSMC). Here, we provide insight into the structure-function properties by which apoE mediates these effects. ApoE3 is most effective in promoting COX-2 expression as a lipid-free pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…S2E vs. S2F). Previously, we reported that apoE3 and its N-terminal domain stimulate the expression of Cox2 mRNA and protein in VSMCs (Ali et al, 2008; Kothapalli et al, 2004). Consistent with these results, the Cox2 inhibitor, nimesulide, prevented suppression of the collagen-I and FN genes by apoE3 in VSMCs whereas the Cox1 inhibitor, SC560, was without effect (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…S2E vs. S2F). Previously, we reported that apoE3 and its N-terminal domain stimulate the expression of Cox2 mRNA and protein in VSMCs (Ali et al, 2008; Kothapalli et al, 2004). Consistent with these results, the Cox2 inhibitor, nimesulide, prevented suppression of the collagen-I and FN genes by apoE3 in VSMCs whereas the Cox1 inhibitor, SC560, was without effect (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…3C). Cox2 production in VSMCs leads to the production of PGI 2 , and VSMCs treated with apoE3 have increased amounts of PGI 2 in their conditioned medium (Ali et al, 2008; Kothapalli et al, 2004). The PGI 2 mimetic, cicaprost, phenocopied the effect of apoE3 on collagen-I and FN mRNAs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 and cPLA 2 are tightly regulated by various mediators in several species (Beasley, 1999; Ali et al, 2008; Pavicevic et al, 2008). cPLA 2 hydrolyzes the membrane phospholipids, resulting in the release of AA, which is further converted by the constitutive enzyme COX-1 or by the inducible COX-2, and PG synthases to biologically active PGs (DeWitt, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Lipid-free apoE is more effective than the lipid associated protein. Whatever receptor mediates this effect, it does not appear to be the LDL receptor, LRP1, or HSPG (40).…”
Section: Smcsmentioning
confidence: 97%